Reflections about teaching physics for blind students - Vitor Fabrício Machado Souza Machado Souza; Ricardo Roberto Plaza Teixeira (Universidade Federal de Santa Maria (UFSM), 2008)
This present study brings surveys, descriptions and alternatives to the political, pedagogical and didactical challenges tangible to the practice of Physics teaching to include visual deficient students in the formal school environment. It will be surveyed a list of situations that demands deep discussions among the teaching staff in order to structure, to the hole class, the most efficient way of learning. Communication, curriculum, didactic materials, visual acuity specifications of each student, ways of evaluation and equilibrium of different pedagogical practices will be the objects of reflection of this study.